2020
DOI: 10.5551/jat.rv17043
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons of Arterial Stiffness Developed Using Cardio-Ankle Vascular Index (CAVI)

Abstract: Arterial stiffness is recognized mainly as an indicator of arteriosclerosis and a predictor of cardiovascular events. Cardio-ankle vascular index (CAVI), which reflects arterial stiffness from the origin of the aorta to the ankle, was developed in 2004. An important feature of this index is the independency from blood pressure at the time of measurement. A large volume of clinical evidence obtained using CAVI has been reported. CAVI is high in patients with various atherosclerotic diseases including coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 127 publications
6
120
0
16
Order By: Relevance
“…Arterial stiffness is mainly recognized as an indicator of arteriosclerosis and a predictor of CV events. Cardio-ankle vascular index (CAVI) is a new arterial stiffness index, and the equation is essentially derived from the stiffness parameter 14,15) . Therefore, CAVI is independent of blood pressure at the time of measurement 16) and indicates the intrinsic stiffness of the aortic wall.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial stiffness is mainly recognized as an indicator of arteriosclerosis and a predictor of CV events. Cardio-ankle vascular index (CAVI) is a new arterial stiffness index, and the equation is essentially derived from the stiffness parameter 14,15) . Therefore, CAVI is independent of blood pressure at the time of measurement 16) and indicates the intrinsic stiffness of the aortic wall.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Therefore, CAVI is independent of blood pressure at the time of measurement 16) and indicates the intrinsic stiffness of the aortic wall. Increased CAVI is observed in persons with CVD and risk factors such as dyslipidemia, and the improvement of risk factors reduces CAVI 15,17) . Miyashita et al 18) reported that pitavastatin treatment significantly decreased CAVI, as well as marker of between groups, and the incidence of 3P-MACE [pitavastatin, 1.6% (n 2); atorvastatin, 6.1% (n 8); P 0.038] (Fig.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAVI has been used in clinical settings and recognized as a strong predictor of cardiovascular events 36) . Otsuka and colleagues 5) investigated changes in CAVI after management of atherosclerotic risk factors and whether these changes influenced the incidence of future cardiovascular events in patients with coronary artery disease (mean age 65 years).…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 99%
“…A recent review article published in the Journal of Atherosclerosis and Thrombosis summarized that CAVI is associated with the presence of atherosclerotic diseases including coronary artery disease, cerebral infarction, chronic kidney disease, and thickening of the carotid intima-media thickness, and coronary risk factors, such as hypertension, diabetes mellitus, uric acid disorders, sleep apnea syndrome, smoking, and obesity in several cross-sectional studies 3) . In addition, several prospective studies demonstrated that CAVI is a predictor of cardiovascular outcomes 3) including that CAVI is an independent long-term predictor of major adverse cardiovascular events, particularly cardiovascu-lar death, in patients with acute coronary syndrome 4) . Moreover, high CAVI (cut-off point of ≥ 9) was reported to be independently associated with a rapid decline in glomerular filtration rate in patients at high risk of cardiovascular disease with or without chronic kidney disease, which suggested that systemic vascular stiffness predicted a decrease in renal function in this population 5) .…”
mentioning
confidence: 99%